The multicultural cookbook for students - Albyn, Carole Lisa.; Webb, Lois Sinaiko (Phoenix, Ariz. : Oryx, 1993)
Presents a collection of recipes from over 120 countries and briefly discusses the culture and culinary habits of each country.
Includes index.
Elem. School Library Collection.
Wilson's Junior High School.
Wilson's Senior High School.
Booklist, October 2006.
Elem. School Library Collection, June 2000.
Keywords: Food crops -- Juvenile literature; Food habits -- Juvenile literature; International cooking -- Juvenile literature; Food habits; International cooking; Eating customs; International cooking